(untitled) (Environmental and Public Health Maritime Journal, 2025)
BACKGROUND: Domestic activities of coastal and island communities are factors that affect the quality and quantity of groundwater availability, including the use of detergents. Chemicals used in detergents can have a negative impact, both on public health and the environment. The dynamic spatial model is a solution to overcome the problem of detergent contamination. AIM: This study aims to build a dynamic model of the distribution of detergent pollutants in well water and their impact on public health in small islands. METHODS: This research is observational research using spatial analysis approach with kriging interpolation method and dynamic modeling with stock flow. Simple random sampling (simple random sampling). RESULTS: The results of the spatial modeling show that the patternthe distribution of contamination is higher in the east to the center of the island. The dynamic modeling results show that the detergent concentration distribution pattern in well water with the lowest concentration is 0.0 mg/l and the highest is 0.16389 mg/l. The pessimistic scenario experienced the highest increase of 0.21 mg/l, while the optimistic scenario experienced the highest increase of 0.03 mg/l. An optimistic scenario is built with 75% off-island laundry activities and WWTP management. CONCLUSION: Based on the results of the analysis, laundry activities and WWTP management must be considered in order to minimize detergent contamination on small islands.